A meta-analysis for the effect of prophylactic GTN on the incidence of post-ERCP pancreatitis and on the successful rate of cannulation of bile ducts - Chen, Bin (BioMed Central, 2010)
BACKGROUND: Glyceryl trinitrate (GTN) has been shown to be able to relax the sphincter of Oddi (SO) both in animals and humans. Theoretically, the use of these compounds during and after endoscopic retrograde cholangiopancreatgraphy (ERCP) could relax the biliary and pancreatic sphincters, facilitating cannulation of common bile duct (CBD) during the procedure, or minimizing potential pancreatic outflow obstruction after the procedure. However, clinical trials evaluating the protective effect of GTN on the post-endoscopic retrograde cholangiopancreatgraphy pancreatitis (PEP) have yielded inconclusive results. This meta-analysis is to systematically assess the effect of prophylactic administration of glyceryl trinitrate (GTN) on the prevention of PEP and the effect on the cannulation of bile ducts. METHODS: By searching PubMed (1966 to September 2009), CENTRAL (Cochrane Controlled trials Register; issue 3, 2009) and EMBASE.com (1984 to September 2009), two independent reviewers systematically identified prospective randomized controlled trials (RCTs) detecting the effect of prophylactic GTN on the incidence of PEP and on the cannulation of bile ducts. A meta-analysis of these clinical trials was then performed. RESULTS: There are 55/899(6.1%) patients suffering PEP in the treatment group versus 95/915(10.4%) patients in the placebo group. The overall pooled risk of PEP was significantly lower in the GTN group than in the placebo group (OR 0.56, 95% CI: 0.40 to 0.79, p = 0.001). Subgroup analyses suggested that GTN administered by the sublingual form (OR 0.34,95% CI:0.16 to 0.75, p = 0.007) is more effective than transdermal route(OR 0.64,95% CI:0.40 to 1.01, p = 0.05), and the protective effect of GTN was far more obvious in the centers with high incidence of PEP (OR 0.40, 95% CI:0.24 to 0.67, p = 0.0006) than those centers with a low incidence of PEP (OR 0.75, 95% CI: 0.47 to 1.20, p = 0.22). Additionally, the meta-analysis suggests that GTN was not helpful for the cannulation of bile ducts. CONCLUSION: We concluded that prophylactic administration of GTN may significantly reduce the incidence of PEP and not be helpful for the cannulation of bile ducts.